The Effect Of Special Exercises For Developing Working Arm Accuracy And Forehand Stroke In Table Tennis - Abedulameer, Hydar (Journal of Physical Education, 2017)
The importance of the study lies in designing exercises to develop the accuracy of working hand young tennis players as well as identifying this trait in forehand stoke. The problem of the research lies in weakness in forehand stoke in this age group thus he aimed at designing exercises that develop this stroke in young table tennis players. The researcher used the experimental method. The subjects were (12) young table tennis players. The data was collected and treated using proper statistical operations. The researcher concluded that the special exercises have a positive effect on developing the accuracy of the working arm. Finally he recommended using these exercises in training program for this age group